Chemopreventive evaluation of a Schiff base derived copper (II) complex against Azoxymethane-induced colorectal cancer in rats - Hajrezaie, M.; Hassandarvish, P.; Moghadamtousi, S.Z.; Gwaram, N.S.; Golbabapour, S.; NajiHussien, A.; Almagrami, A.M.; Zahedifard, M.; Rouhollahi, E.; Karimian, H.; Fani, F.; Kamalidehghan, B.; et al. (Public Library of Science, 2014)
Background: Based on the potential of Schiff base compounds to act as sources for the development of cancer chemotherapeutic agents, this in vivo study was performed to investigate the inhibitory properties of the synthetic Schiff base compound Cu(BrHAP)2 on colonic aberrant crypt foci (ACF). Methodology: This study involved five groups of male rats. The negative control group was injected with normal saline once a week for 2 weeks and fed 10% Tween 20 for 10 weeks, the cancer control group was subcutaneously injected with 15 mg/kg azoxymethane once per week for two consecutive weeks, the positive control group was injected with 15 mg/kg azoxymethane once per week for two consecutive weeks and 35 mg/kg 5-fluorouracil (injected intra-peritoneally) for 4 weeks, and the experimental groups were first injected with 15 mg/kg azoxymethane once per week for two consecutive weeks and then fed 2.5 or 5 mg/kg of the Schiff base compound once a day for 10 weeks. Application of the Schiff base compound suppressed total colonic ACF formation by up to 72% to 74% (P,0.05) when compared with the cancer control group. Analysis of colorectal specimens revealed that treatments with the Schiff base compound decreased the mean crypt scores in azoxymethane-treated rats. Significant elevations of superoxide dismutase, glutathione peroxidase and catalase activities and a reduction in the level of malondialdehyde were also observed. Histologically, all treatment groups exhibited significant decreases in dysplasia compared to the cancer control group (P,0.05). Immunohistochemical staining demonstrated down-regulation of the PCNA protein. Comparative western blot analysis revealed that COX-2 and Bcl2 were up-regulated and Bax was down-regulated compared with the AOM control group. Conclusion: The current study demonstrated that the Cu(BrHAP)2 compound has promising chemoprotective activities that are evidenced by significant decreases in the numbers of ACFs in azoxymethane-induced colon cancer.